Preliminary development of a reconfigurable garment system for interactive biomechanics - Helmer, R.; Blanchonette, I.; Farrow, D.; Ball, K.; Mackay, C. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
This paper presents a garment system that uses electronic textile strain sensors attached to a host garment to enable interactive biomechanical monitoring and biofeedback. A conventional compression garment modified to include strategically placed fastening markers and a corresponding e-textile strain sensor were used to monitor knee flexion and extension during AFL kicking. The output of the garment system was compared with that of a Vicon. During repeated subject kicking the garment system displayed stable operation suggesting it was suitable for use in field based skill interventions involving interactive biofeedback.